2011
DOI: 10.1007/s12011-011-9123-9
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Levels of Zn and Cu and Severity of Coronary Atherosclerosis

Abstract: The essential trace elements play important roles in the maintainance of the normal structure and physiology of cells. Several research groups have demonstrated that they also play important roles in states of cardiovascular diseases. Our aim is to investigate whether there is a relationship between trace elements (Zn and Cu) and the degree of atherosclerosis. The sample consisted of 67 patients with coronary artery disease and 26 clinically healthy individuals. Ninety-three subjects were separated into four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
2
20
2
Order By: Relevance
“…The serum levels of zinc and copper were found to be significantly lower in patients with atherosclerosis than in the control group, but there were no significant differences in the serum levels of Cu and Zn between severe atherosclerosis and mild atherosclerosis. The present study revealed a relationship between the serum levels of zinc and copper and atherosclerosis, but not between these levels and the severity of the disease [214].…”
Section: Cardiovascular System Disorderscontrasting
confidence: 84%
“…The serum levels of zinc and copper were found to be significantly lower in patients with atherosclerosis than in the control group, but there were no significant differences in the serum levels of Cu and Zn between severe atherosclerosis and mild atherosclerosis. The present study revealed a relationship between the serum levels of zinc and copper and atherosclerosis, but not between these levels and the severity of the disease [214].…”
Section: Cardiovascular System Disorderscontrasting
confidence: 84%
“…Trace elements have been proposed to have diagnostic and prognostic value in ischemic heart disease [7,8]. Epidemiological studies support the possibility of imbalances in trace element levels which may increase the risk of CVD, like Fe, Pb, and Cd that show elevated levels in myocardial infarction (MI) patients than in controls [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[45][46] In contrast, a study of Islamoglu et al 2011 found that serum Zn was significantly lower in patients than in healthy control (P < 0.010). 47 Moreover, in the study of Bayir et al 2013, serum Zn concentration was significantly less in the CHD group compared to the control group (p< 0.010). 30 Also, Lui et al 2015 meta-analysis study indicated that subjects with MI had lower Zn levels than healthy controls (SMD=−1.848, 95 % CI=(−2.365, −1.331).…”
Section: Discussionmentioning
confidence: 90%